Short impact on soil microbiome of a Bacillus amyloliquefaciens QST713 based product that correlates with higher potato yield across USA - Adamo, Irene; Acin-Albiac, Marta; Röttjers, Sam; de Prado, Diego Rodríguez; Benito, Blas M.; Zamora, Jorge; Godara, Rakesh; García-Jiménez, Beatriz; Jiang-Rempel, Panpan; Cline, Lauren C.; Acedo, Alberto (Frontiers in Plant Science, 2024)
PPotato (Solanum tuberosum L.) is considered one of the most widely consumed crops worldwide, due to its high yield and nutritional profile, climate change-related environmental threats and increasing food demand. This scenario highlights the need of sustainable agricultural practices to enhance potato productivity while, preserving and maintining soil health. Plant growth- promoting bacteria (PGPB) stimulate crop production through biofertilization mechanisms with low environmental impact. For instance, PGPB promote biological nitrogen fixation, phosphate solubilization, production of phytohormones, and biocontrol processes. Hence, these microbes provide a promising solution for more productive and sustainable agriculture. In this study, the effects of Bacillus amyloliquefaciens QST713 based-product (MINUET™, Bayer) were assessed in terms of yield, soil microbiome, potato peel and petiole nutrient profile as a promising PGPB in a wide range of potato cultivars across the United States of America. Depending on the location, potato yield and boron petiole content increased after biostimulant inoculation to maximum of 24% and 14%, respectively. Similarly, nutrient profile in potato peel was greatly improved depending on the location with a maximum of 73%, 62% and 36% for manganese, zinc and phosphorus. Notably, fungal composition was shifted in the treated group. Moreover, yield showed strong associations with specific microbial taxa, such as Pseudoarthrobacter, Ammoniphilus, Ideonella, Candidatus Berkiella, Dongia. Moreover, local networks strongly associated with yield, highlighting the important role of the native soil microbiome structure in indirectly maintaining soil health. Our results showed that treatment with B. amyloliquefaciens based product correlated with enhanced yield, with minor impacts on the soil microbiome diversity. Further studies are suggested to disentangle the underlying mechanisms of identified patterns and associations.